2019
DOI: 10.3390/en12163182
|View full text |Cite
|
Sign up to set email alerts
|

Robust Direct Adaptive Controller Design for Photovoltaic Maximum Power Point Tracking Application

Abstract: Tracking the maximum output power of a photovoltaic (PV) cell is an important problem to harvest more energy at different weather and load conditions. This paper presents the design and simulation of a robust direct adaptive controller (RDAC) for maximum power point tracking (MPPT) device based on boost converter topology. A mathematical model is developed, and a suitable RDAC is designed for MPPT device, and simulations are performed using MATLAB/Simulink to verify the controller’s robustness at varying opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The PV cell maximum power (213.15 W) versus MPPT output power is shown in Figure 9 for 1000 W/m 2 radiation at 25°C. This finding illustrates that the reaction time of the MRAC adaptive controller is lower than 0.02 sec, which is quicker than any other controller as in [26,31]. Figure 10 shows the voltage and current waveform.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The PV cell maximum power (213.15 W) versus MPPT output power is shown in Figure 9 for 1000 W/m 2 radiation at 25°C. This finding illustrates that the reaction time of the MRAC adaptive controller is lower than 0.02 sec, which is quicker than any other controller as in [26,31]. Figure 10 shows the voltage and current waveform.…”
Section: Resultsmentioning
confidence: 86%
“…R 0 is the load resistance. [26]. A small-signal equivalent circuit is assumed to simplify the study of transient response as indicated in [27].…”
Section: Boost Converter Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have researched the MPPT control issue of the PV system in recent years [3][4][5][6][7][8][9][10][11][12]. The MPPT methods for the PV system are summarized and compared in [13].…”
Section: Introductionmentioning
confidence: 99%